Monument Des Martyrs Dans La Ville d’Abidjan : Entre Logique Urbaine Et Légitimation Politique (2002 À 2010) - Barnabé Cossi Houédin; N’Guessan Daniel Djédjé; Tata Mariam Fofana (European Scientific Journal, ESJ, 2017)
This text handles with the fate of the built monuments to the memory of victims built as martyrs in a context of crisis in Côte d’Ivoire. He is mainly interested in the way the political systems legitimize them since their construction. As regards him "Monument of the martyrs", the results show a kind of legitimization of the power in sync with the mobilization of urban logics. Which passes by the gratitude and the valuation to the deaths set up as martyrs and by the strategies of identification, resistance and identity domination. The article tends to highlight a variability of the fields of use of the monument as social resource and the representations which are associated with it, the links built between such representations and the arrangement of the city during period going from 2002 till 2010. As a matter of fact, the text shows that the legitimization of the monument in the urban dynamics favors rationalities the coherence of which strengthens the public action regarding governance, regarding production of a shape of citizenship, a type of collective identity and spatial marking